2011
DOI: 10.3844/ajidsp.2011.104.106
|View full text |Cite
|
Sign up to set email alerts
|

Drug Susceptibility Pattern of <i>M.Tuberculosis</i> Isolated from Patients Attending a Private Hospital

Abstract: Problem statement: Drug resistance in Tuberculosis (TB) is an emerging problem that adversely affects patient outcome and public health in the developing world. Although much of tuberculosis care is provided by the private sector in India, the magnitude of drug resistance in TB in the private sector is not well described. The present study was carried out to determine the resistance pattern of tuberculosis in patients attending a large tertiary care hospital in South India. Approach: Anti-tuberculosis resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…12 Streptomycin resistance is a concern as it is an essential component of category II DOTS regimen. 13 In this study, drug resistance among new cases was found to be 46.53% while drug resistance in previously treated cases was 67.24%. Similar finding has been reported in a study in which 36.84% isolates were drug resistant in new cases and 75.16% isolates were drug resistant in previously treated cases.…”
Section: Discussionmentioning
confidence: 53%
“…12 Streptomycin resistance is a concern as it is an essential component of category II DOTS regimen. 13 In this study, drug resistance among new cases was found to be 46.53% while drug resistance in previously treated cases was 67.24%. Similar finding has been reported in a study in which 36.84% isolates were drug resistant in new cases and 75.16% isolates were drug resistant in previously treated cases.…”
Section: Discussionmentioning
confidence: 53%